The importance of nutritional interventions for incarcerated youth. Issue 5 (16th April 2018) - Magaziner, Sarah
Abstract : The consumption of adequate nutrition in adolescence can have long‐term positive effects on physical and emotional development, contributing to the prevention of several chronic diseases, including obesity, coronary heart disease, stroke, and Type 2 diabetes. While many of these diseases are not detected until adulthood, childhood obesity has emerged as a significant public health issue. The prevalence of obesity has doubled among American youth in the past three decades, with the most recent data confirming that one in three children in the United States are clinically overweight or obese.